QUALITY STANDARDS FOR MEASURING THE LEVEL OF SERVICE IN PUBLIC TRANSPORT (Perner's Contacts, 2011)
Based on the results of the experimental verification methodology of measuring customer satisfaction and quality evaluation of public transport, quality standards for services’ level measuring have been proposed. Quality standards which I recommend to set legal regulations should be defined by law or binding regulation. Setting standards for the criteria of time availability in the transport network is recommended to transfer in the responsibility of municipal authorities.